Динамика влажности ксилемы ствола у плодовых культур семейства Rosaceae - ИЛЬНИЦКИЙ, ОЛЕГ АНТОНОВИЧ; БОЙКО, МИХАИЛ ФЕДОСЕЕВИЧ (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
Динамика влажности ксилемы ствола у плодовых культур семейства Rosaceae